UFM's solar energy project - Snead, Bruce; Teener, Linda; Dorsett, Bill (Kansas State University, 2009)
This presentation will overview UFM's Solar Energy Project, discuss the practical logistics of using passive and active solar energy production and will look at ways to share this information across Kansas and the region. UFM Community Learning Center's Solar Addition began as a demonstration of alternative energy and energy conservation in 1980 with the construction of the passive solar Green House. The initial project was funded with a grant from the U.S. Department of Energy and the City of Manhattan. It has served as a regional model of innovative uses of passive solar energy for many years. Recently, the facility has been renovated, updating examples of energy efficiency and adding a photovoltaic array to the existing passive solar features. The UFM Solar Project now provides a demonstration of both active and passive solar energy. The photovoltaic project, attached to Westar energy's electrical grid, went live in late July, 2008. Data collected from this project will show the production and cost savings of using solar energy to produce electricity. The UFM Solar Addition Project has two primary goals. The first goal is to create a regional demonstration project of alternative energy technologies. The project provides a demonstration of practical, usable active and passive solar technology available for home and small-scale commercial use. Technologies include passive solar energy collection, using a greenhouse wall with movable insulation, a demonstration of active photovoltaic technology collecting and using the sun's energy for electricity, energy conservation through windows, doors and strategic sun shading. The second goal is to provide unique educational programming to K-State, the Manhattan community and to the region utilizing the updated UFM Solar Addition facility. Classes, tours, demonstrations, and production greenhouse activities are available. Information on the advantages and challenges of alternative energy will be discussed. An outgrowth of the active photovoltaic technology has been the opportunity to advance the agenda of grid-connected solar technology use and energy policy in Kansas. The presenters can provide insight and suggestions on how to work with energy companies to move the region closer to small consumer use of grid-connected solar arrays.
Keywords: Active solar energy; Passive solar energy; Photovoltaics; Demonstration project